Ginsenoside Rg1 attenuates adjuvant-induced arthritis in rats via modulation of PPAR-γ/NF-κB signal pathway - Zhang, Leiming (Oncotarget, 2017)
Ginsenoside Rg1, the main active compound in Panax ginseng, has already been shown to have anti-inflammatory effects. However, the protective effects of Rg1 on rheumatoid arthritis (RA) remain unclear. The aim of the present study was to investigate the effects and mechanisms of Rg1 on adjuvant-induced arthritis (AIA) in rats. AIA rats were given Rg1 at doses of 5, 10, and 20 mg/kg intraperitoneally for 14 days to observe the anti-arthritic effects. The results showed that Rg1 significantly alleviated joint swelling and injuries. Rg1 can also significantly reduce the level of TNF-α and IL-6, increase PPAR-γ protein expression, inhibit IκBα phosphorylation and NF-κB nuclear translocation in the inflammatory joints of AIA rats and RAW264.7 cells stimulated by lipopolysaccharide (LPS). The results indicate that Rg1 has therapeutic effects on AIA rats, and the mechanism might be associated with its anti-inflammatory effects by up-regulating PPAR-γ and subsequent inhibition of NF-κB signal pathway.